Study the therapeutic role of Alcoholic Extract of Plantago lanceolata aganist infection with Staphylococcus saprophyticus: Hassan A. Abdul –Ratha¹ and Aseel J. Mohammad² - Mohammad, Aseel J. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was carried out to investigate the antibacterial activity of alcoholicextracts of Plantago lanceolata leafes in vitro and in vivo by inducing urinary tract infection inrats which caused by urethra administration of S.saprophyticus isolated from human andanimals(cow and sheep)These extracts showed significant effect (P<0.05) on the inhibition of the growth ofS.saprophyticus in vitro with the superiority of the concentration 200mg / ml of alcoholicextract with the mean of inhibition zone diameter 30 mm against S.saprophyticus ,while zonediameter was ( 26.5 ,21 ) mm due to the concentration 150, 100mg/ml respectively.This study included the therapeutic role of doses 150 mg/kg . B.W. of 1.5ml daily orally ofalcoholic extract dissolved in DMSO of plantago lanceolata leaves in the pathogenesis ofS.saprophyticus in rats by the urethral infection in compared with the control group (ratsinjected with S.saprophyticus without treatments).The results of histopathological changesshowed the role of Plantago lanceolata extract on the decreasing of pathological sings inbladder and kidney tissue after 14 and 21 days and gave negative results by decreasecongestion in the blood vessels of kidney hemorrhage and few infiltration of inflammatorycells in bladder , in compared with the positive control which showed acutehistopathological change.